A comparison of tree biometric performance of four tropical energy wood species. Issue 1 (September 2020) - Yulianti, M; Adinugroho, W C; Krisnawati, H
Abstract: Four energy wood species, i.e. Weru (Albizia procera (Roxb.) Benth.), Akor (Acacia auriculiformis Benth), Pilang (Acacia leucophloea (Roxb.) Willd), and Kaliandra, (Calliandra calothyrsus Meisn.) that are suitable for substituting fossil energy in Indonesia were tested in experimental plots in Majalengka, West Java, Indonesia. In this paper, we assessed the performance of the planted species of up to 3.5 years old by measuring and analyzing the significant biometric parameters (height, diameter, volume, and biomass) of the trees growing on the plots. In each measurement, tree diameter and height were recorded. Volume and biomass were calculated by using allometric equations. The results showed that A. auriculiformis performed better than the other three species in terms of height, diameter, volume, and biomass. The performance was then followed by C. calothyrsus, A. procera, and A. leucophloea. The mean annual increment of volume and biomass of A. auriculiformis was 12.90 m 3 /ha/yr and 7.32 tonnes/ha/yr, respectively.